Hawthorne's short stories - Hawthorne, Nathaniel; Arvin, Newton (New York : Vintage Books, 1946)
Twenty four of the best of Hawthorne's short stories.
Keywords: Manners and customs; New England -- Social life and customs -- Fiction; New England; Fiction; Short stories